2020
DOI: 10.1029/2020wr027495
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Montane Forest Conversion Is a Critical Driver for Sediment Supply in East African Catchments

Abstract: Land use change is known to affect suspended sediment fluxes in headwater catchments. There is however limited empirical evidence of the magnitude of these effects for montane catchments in East Africa. We collected a unique 4-year high-frequency data set and assessed seasonal sediment variation, water pathways, and sediment response to hydrology in three catchments under contrasting land use in the Mau Forest Complex, Kenya's largest tropical montane forest. Annual suspended sediment yield was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 82 publications
2
11
0
Order By: Relevance
“…Peak SSC concentrations were reached in early to mid-rainy season (in the months of April-July for long rains and September to October for short rains), in some instances prior to peak flow, and decreased in the transition from rainy to dry season (in the months of December-March). The higher concentrations of suspended sediments during the rainy season and the lower concentrations in the dry season in this study are consistent with other rivers studied in the Mau Forest Complex (Dutton et al, 2018;Stenfert Kroese et al, 2020a). Also notable are the considerable high SSC even in times when flows were consistently lower in March and May 2019 at site CMT and KIP.…”
Section: Spatial and Temporal Trends Of Suspended Sediment Concentrationssupporting
confidence: 90%
See 2 more Smart Citations
“…Peak SSC concentrations were reached in early to mid-rainy season (in the months of April-July for long rains and September to October for short rains), in some instances prior to peak flow, and decreased in the transition from rainy to dry season (in the months of December-March). The higher concentrations of suspended sediments during the rainy season and the lower concentrations in the dry season in this study are consistent with other rivers studied in the Mau Forest Complex (Dutton et al, 2018;Stenfert Kroese et al, 2020a). Also notable are the considerable high SSC even in times when flows were consistently lower in March and May 2019 at site CMT and KIP.…”
Section: Spatial and Temporal Trends Of Suspended Sediment Concentrationssupporting
confidence: 90%
“…Forests and riparian buffer zones can act as a filter, controlling and decreasing the sediment load by surface runoff (Mello et al, 2018). Similar effects were reported in previous studies that found forested watersheds to have lower suspended sediment concentrations as compared to agricultural landscapes (Tu, 2013;Zhang et al, 2017;Mello et al, 2018;Stenfert Kroese et al, 2020a). Contrasting the effect of land use, we have no clear explanation for the positive correlation with catchment size.…”
Section: Spatial and Temporal Trends Of Suspended Sediment Concentrationssupporting
confidence: 81%
See 1 more Smart Citation
“…Invasive alien plant species have equally been identified to contribute to freshwater pollution (Chamier et al, 2012). Land use/cover change resulting to increase sediment loads from upstream catchments is also a major source of water pollution (Dutton et al, 2018; Stenfert Kroese et al, 2020).…”
Section: Water Security Challenges Facing Sub‐saharan Africamentioning
confidence: 99%
“…Lack of land-use effects on decomposition rates in this study is intriguing and contrary to similar studies on the effects of agriculture on organic matter processing in tropical (Jinggut et al, 2012;Masese et al, 2014b;Silva-junior et al, 2014;Fugère et al, 2020) and temperate (Woodward et al, 2012;Ferreira et al, 2015) streams. Although our agricultural sites had significantly elevated levels of total suspended solids and electrical conductivity, which are indicators of anthropogenic activities on water quality (Minaya et al, 2013;Ontumbi et al, 2015;Masese et al, 2017;Kroese et al, 2020), these were deemed within tolerable limits of most sensitive taxa, including shredders, in these sites. Riparian zones in agricultural streams were well maintained, and this increased the quality of instream habitats, canopy cover and standing stocks of organic matter (Table 1) that are depended upon by shredders.…”
Section: Discussionmentioning
confidence: 81%